Optimizing the Rearrangement Process in a Dedicated Warehouse (2010)
Determining the optimal storage assignment for products in a dedicated warehouse has been addressed extensively in the Facility Logistics literature. However, the process of implementing a particular storage assignment given the current location of products has not received much attention in the existing literature. Typically, warehouses use downtime or overtime to remove products from their current location and move them to the suggested location. This work presents the Rearrange-While-Working (RWW) policy to optimize the process of rearranging a dedicated warehouse. The RWW policy seeks to relocate products in a warehouse from the initial arrangement to the optimal arrangement while serving a list of storages and retrievals. This study considers three scenarios: (1) when there is only one empty location in the warehouse and the material handling equipment (MHE) is idle (i.e. reshuffling policy); (2) when there is only one empty location in the warehouse under the RWW policy; (3) when there are multiple empty locations in the warehouse under the RWW policy. In the first case, the MHE can make any movement desired as it is idle. In the other cases, the movements correspond to a list of storages and retrievals that need to be served. In these cases it is assumed that products can only be moved when they are requested. After being used, they are returned to the warehouse. Several heuristics are presented for each scenario. The proposed heuristics are shown to perform satisfactorily in terms of solution quality and computational time.